3D Printing of Intracranial Aneurysms Using Fused Deposition Modeling Offers Highly Accurate Replications - Frölich, A.M.J.; Spallek, J.; Brehmer, L.; Buhk, J.-H.; Krause, D.; Fiehler, J.; Kemmling, A. (American Journal of Neuroradiology, 2016)
BACKGROUND AND PURPOSE: As part of a multicenter cooperation (Aneurysm-Like Synthetic bodies for Testing Endovascular devices in 3D Reality) with focus on implementation of additive manufacturing in neuroradiologic practice, we systematically assessed the technical feasibility and accuracy of several additive manufacturing techniques. We evaluated the method of fused deposition modeling for the production of aneurysm models replicating patient-specific anatomy.MATERIALS AND METHODS: 3D rotational angiographic data from 10 aneurysms were processed to obtain volumetric models suitable for fused deposition modeling. A hollow aneurysm model with connectors for silicone tubes was fabricated by using acrylonitrile butadiene styrene. Support material was dissolved, and surfaces were finished by using NanoSeal. The resulting models were filled with iodinated contrast media. 3D rotational angiography of the models was acquired, and aneurysm geometry was compared with the original patient data.RESULTS: Reproduction of hollow aneurysm models was technically feasible in 8 of 10 cases, with aneurysm sizes ranging from 41 to 2928 mm3 (aneurysm diameter, 3–19 mm). A high level of anatomic accuracy was observed, with a mean Dice index of 93.6% ± 2.4%. Obstructions were encountered in vessel segments of <1 mm.CONCLUSIONS: Fused deposition modeling is a promising technique, which allows rapid and precise replication of cerebral aneurysms. The porosity of the models can be overcome by surface finishing. Models produced with fused deposition modeling may serve as educational and research tools and could be used to individualize treatment planning.FDMfused deposition modelingIDidentification